2020
DOI: 10.1126/sciadv.aaz5344
|View full text |Cite
|
Sign up to set email alerts
|

Ancient genome-wide DNA from France highlights the complexity of interactions between Mesolithic hunter-gatherers and Neolithic farmers

Abstract: Starting from 12,000 years ago in the Middle East, the Neolithic lifestyle spread across Europe via separate continental and Mediterranean routes. Genomes from early European farmers have shown a clear Near Eastern/Anatolian genetic affinity with limited contribution from hunter-gatherers. However, no genomic data are available from modern-day France, where both routes converged, as evidenced by a mosaic cultural pattern. Here, we present genome-wide data from 101 individuals from 12 sites covering today’s Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
126
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(151 citation statements)
references
References 106 publications
16
126
0
1
Order By: Relevance
“…1500 years. However, the first recently published genetic evidence from northern France 53,54 , demonstrates much more hunter-gatherer ancestry in early farmer's genes in western Europe compared to central and SE Europe, which fits the conclusions of the present study. Interestingly, the predominance of cattle over sheep/goat within the assemblage of Bazel perfectly mirrors the livestock within the different succeeding agro-pastoral cultures of the loess region, characterized by a cattle-based economy in which sheep/goat only played a minor role (ca.…”
Section: Discussionsupporting
confidence: 91%
“…1500 years. However, the first recently published genetic evidence from northern France 53,54 , demonstrates much more hunter-gatherer ancestry in early farmer's genes in western Europe compared to central and SE Europe, which fits the conclusions of the present study. Interestingly, the predominance of cattle over sheep/goat within the assemblage of Bazel perfectly mirrors the livestock within the different succeeding agro-pastoral cultures of the loess region, characterized by a cattle-based economy in which sheep/goat only played a minor role (ca.…”
Section: Discussionsupporting
confidence: 91%
“…2012), but in extremely low frequencies in Europe, with H1 only being found associated with the spread of the Romani people ~900 ya. Conversely, H2 has been present in Europe since at least 10 kya (Lazaridis et al 2016), and is strongly linked with the spread of agriculture (Hofmanová et al 2016; Rivollat et al 2020), but is found at no higher than 0.2% frequency in modern-day western European populations. In contrast, H2 was more common in Neolithic groups, and has been found to have constituted between 1.5% and 9% of the observed Y haplogroups, with the exception of the highly related samples from Rivollat et al, for which H2 was ~30% (Brunel et al 2020, Haak et al 2015, Mathieson et al 2015, Lazaridis et al 2016, Lipson et al 2017, Olalde et al 2019, Rivollat et al 2020, Skourtanioti et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The relative scarcity of H2 individuals, especially compared to the relatively high frequency of the accompanying G2a individuals, allows us to better track the ‘genealogical history’ and thus potential dispersal routes as we would expect a stronger effect of lineage sorting and therefore a higher chance of observing geographic patterns. In this particular case, we could trace expanding Neolithic farmers from Anatolia to Western Europe through the use of unique markers associated with H2 individuals and test whether we can genetically discern the proposed so-called “Danubian or inland’’ and “Mediterranean’’ routes of the Neolithic expansion (Price 2000), which had recently also found support by genomic signals from the nuclear genome (Rivollat et al 2020). Unfortunately, we found that the H2 subsection of the evolutionary tree for the Y chromosome is currently poorly understood (due to the scarcity of modern samples of H2 individuals and the relative rarity of ancient H2 individuals), and, in many cases, inconsistent with a tree-like history for almost all of the published and unpublished ancient samples.…”
Section: Resultsmentioning
confidence: 99%
“…The admixture events were geographically highly localized and involved various populations with different ancestry components 3 . These processes likely led to the increase in HG ancestry proportions and mtDNA lineages that were observed in Middle to Late Neolithic communities 1 , 7 , 35 , 36 . It is currently not known what might have influenced these widespread demographic and genomic processes in Europe, but climate change and/or social processes may be considered contributing factors 37 .…”
Section: Discussionmentioning
confidence: 99%